2008
DOI: 10.3390/md6030496
|View full text |Cite
|
Sign up to set email alerts
|

The Mauve Stinger Pelagia noctiluca (Forsskål, 1775). Distribution, Ecology, Toxicity and Epidemiology of Stings.

Abstract: Abstract:The toxicity of Cnidaria is a subject of concern due to its influence on humans. In particular, jellyfish blooms can highly affect human economical activities, such as bathing, fishery, tourism, etc., as well as the public health. Stinging structures of Cnidaria (nematocysts) produce remarkable effects on human skin, such as erythema, swelling, burning and vesicles, and at times further severe dermonecrotic, cardio-and neurotoxic effects, which are particularly dangerous in sensitive subjects. In seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 56 publications
1
62
1
2
Order By: Relevance
“…Populations occur in both the North and South Atlantic (Miller et al 2012), as well as in all the major oceans (Mayer 1910). The species has a negative impact on tourism (Bernard et al 2011) because of its painful stings (Maretic et al 1991, Mariottini et al 2008), on aquaculture by overwhelming fish farms and killing fish (Doyle et al 2008, Delannoy et al 2011, and potentially on the success of fish stocks such as tuna (Gordoa et al 2013). In the Mediterranean Sea, P. noc-tiluca has been a recurrent problem for centuries (Goy et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Populations occur in both the North and South Atlantic (Miller et al 2012), as well as in all the major oceans (Mayer 1910). The species has a negative impact on tourism (Bernard et al 2011) because of its painful stings (Maretic et al 1991, Mariottini et al 2008), on aquaculture by overwhelming fish farms and killing fish (Doyle et al 2008, Delannoy et al 2011, and potentially on the success of fish stocks such as tuna (Gordoa et al 2013). In the Mediterranean Sea, P. noc-tiluca has been a recurrent problem for centuries (Goy et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the bloom of jellyfish Cyanea nozakii in Liaodong Bay of Bohai Sea in 2004, which was regarded as the main cause for the approximately 80% decline of edible jellyfish Rhopilema esculentum and the direct economic losses were approximately US$70 million (Ge and He, 2004). Moreover, venomous jellyfish can produce skin erythema, swelling, burning and vesicles, and at times, severe dermonecrotic, cardio-and neurotoxic effects, which are occasionally fatal for some patients (Mariottini et al, 2008). The published hospital reports showed that over 2000 cases of jellyfish stings occurred in the popular coastal areas of China since 1983, including 13 fatal cases (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…5,[39][40][41][42][43] In addition, the activity of crude venom on other cnidarians has been assessed.…”
Section: Toxicological Aspectsmentioning
confidence: 99%
“…5,6 It is a small pelagic medusa (3-12 cm diam- eter of adult umbrella), whose colour varies from pink to brown to violet. It can be observed mainly during spring and summers.…”
Section: Introductionmentioning
confidence: 99%